Impact of gate dielectric material on basic parameters of MO(I)SHEMT devices - Agopian, Paula Ghedini Der [UNESP]; Carmo, Genilson Julião Do [UNESP]; Martino, Joao Antonio; Simoen, Eddy; Collaert, Nadine (The Electrochemical Society, 2020)
In this work, the behavior of MISHEMT devices with different gate materials is analyzed. Two-gate insulator materials (Al2O3 and SiN) were analyzed through the transfer characteristic, threshold voltage, hysteresis and transconductance. Although devices with SiN insulator present smaller hysteresis, better DIBL and it is nearest to a normally off devices, the leakage current showed to be much higher than for the Al2O3 counterpart. Besides the double conduction that occurs in SiN devices results in an anomalous behavior of transconductance and consequently an unexpected behavior of threshold voltage with temperature.